177Lu-labeled PSMA targeting therapeutic with optimized linker for treatment of disseminated prostate cancer; evaluation of biodistribution and dosimetry - Abouzayed, Ayman; Seitova, Kamila; Lundmark, Fanny; Bodenko, Vitalina; Oroujeni, Maryam; Tolmachev, Vladimir; Rosenström, Ulrika; Orlova, Anna (Frontiers in Oncology, 2023)
Prostate specific membrane antigen (PSMA), highly expressed in metastatic castration-resistant prostate cancer (mCRPC), is an established therapeutic target. Theranostic PSMA-targeting agents are widely used in patient management and has shown an improved outcomes for mCRPC patients. Earlier, we optimized a urea-based probe for radionuclide visualization of PSMA-expression in vivo using computer modelling. With the purpose to develop a targeting agent equally suitable for radionuclide imaging and therapy, the agent containing DOTA chelator was designed (BQ7876). The aim of the study was to test the hypothesis that 177 Lu-labelled BQ7876 possesses target binding and biodistribution properties potentially enabling its use for radiotherapy.BQ7876 was synthesized and labelled with Lu-177. Specificity and affinity of [ 177 Lu]Lu-BQ7876 to PSMA-expressing PC3-pip cells was evaluated and its processing after binding to cells was studied. Animal studies in mice were performed to assess its biodistribution in vivo, target specificity and dosimetry. [ 177 Lu]Lu-PSMA-617 was simultaneously evaluated for comparison.BQ7876 was labelled with Lu-177 with radiochemical yield >99%. Its binding to PSMA tested was specific in vitro and in vivo when tested in antigen saturation conditions as well as in PSMA-negative PC-3 tumors. The binding of [ 177 Lu]Lu-BQ7876 to living cells was characterized by rapid This is a provisional file, not the final typeset article association, while the dissociation included a rapid and a slow phase with affinities KD1=3.8 nM and KD2=25 nM. The half-inhibitory concentration for nat Lu-BQ7876 was 59 nM that is equal to 61 nM for nat Lu-PSMA-617. Cellular processing of [ 177 Lu]Lu-BQ7876 was accompanied by slow internalization. [ 177 Lu]Lu-BQ7876 was cleared from blood and normal tissues rapidly. Initial elevated uptake in kidneys decreased rapidly, and by 3 h pi, the renal uptake (13±3%ID/g) did not differ significantly from tumor uptake (9±3%ID/g). Tumor uptake was stable between 1 and 3 h followed by a slow decline. The highest absorbed dose was in kidneys, followed by organs and tissues in abdomen. Biodistribution studies in mice demonstrated that targeting properties of [ 177 Lu]Lu-BQ7876 are not inferior to properties of [ 177 Lu]Lu-PSMA-617, but do not offer any decisive advantages.